The mitochondrial genome of the springtail Bourletiella arvalis (Symphypleona, Collembola). Issue 2 (3rd July 2019) - Leo, Chiara; Nardi, Francesco; Frati, Francesco; Fanciulli, Pietro Paolo; Cucini, Claudio; Vitale, Matteo; Brunetti, Claudia; Carapelli, Antonio
Abstract: The complete mitochondrial genome of the springtail Bourletiella arvalis (Fitch, 1863) is herein described and applied to a Bayesian phylogenetic analysis, inclusive of all the Collembola mitochondrial DNAs sequenced so far. The gene content and order, as well as the nucleotide composition, conform with the well-known features of hexapods' mitochondrial genomes. The phylogenetic analysis supports the monophyly of Collembola, Poduromorpha, Entomobryomorpha and Symphypleona. However, no mtDNA from Neelipleona is available to date, therefore limiting the application of mitochondrial genomes to further investigate springtail systematics.